Older Adults and Digital Game: Trends, Challenges and Benefits - Nurul Farinah, Mohsin; Suriati Khartini, Jali; Mohamad Imran, Bandan; Nurfauza, Jali; Amelia Jati, Robert Jupit (2021)
The usage of digital games is not limited to entertainment purposes. It can be used in healthcare and social science studies focusing on older adults as the main subject. The objectives of this review are to identify the challenges related to older adults, the benefits they gained using the digital game, and the method used in previous studies. There are 27 articles reviewed based on keywords searched in Scopus database. These studies are evaluated regarding their approaches, challenges and benefits of digital games highlighted in their studies. Finally, several improvable points in the current approaches are highlighted and suggestions are provided as further works.